Nanostructural characterization of antimicrobial and antioxidant copper nanoparticles synthesized using novel Persea americana seeds - S. Rajeshkumar; G. Rinitha (Elsevier, 2018)
In this present investigation, we have synthesized the copper nanoparticles using the eco-friendly green method. This work explains that biosynthesis of copper nanoparticles by using Persea americana of seed extract with easier and green technique. The nanoparticles can be characterized by UV-vis spectroscopy, XRD, FT-IR, SEM, and TEM. Copper nanoparticles are the spherical shape and crystalline in nature, the size range of these particles around 42-90 nm the elemental and chemical composition was characterized by FT-IR. The copper nanoparticles are having good antifungal and antibacterial activity against the diseases causing pathogens. The antioxidant activity of Persea americana mediated copper nanoparticles was evaluated by using DPPH assay. Keywords: Copper nanoparticles, Green synthesis, Structure, Antifungal, Antibacterial, Antioxidant